Exploring thr factors influencing the academic performance of Libyan postgraduate students in Malaysia - Amna Salh Abdulrahim Hamei (2018)
The objective of this study is to explore the factors that influence the academic performance of Libyan postgraduate students in selected Malaysia universities. A case study qualitative research design was used to answer four research questions. Open-ended interview questions were used to collect data from the 11 participants as a sample of the study using a purposive sampling technique. The qualitative data analysis was used to reflect factors that influence the. academic performance of the participants. The results showed that academic satisfaction and self-motivation, customs, religion, and adaptation issues, and political situation in Libya and psychological tension are the contributing factors that influenced the academic performance of Libyan postgraduate students in selected Malaysia universities. The study also found that family responsibilities and psychological pressure, lack of English proficiency skills and academic stress, financial decision and fear of the future, family conflicts and partner attention deficit disorder, and lack of qualifying test before leaving Libya constitute to the factors affecting Libyan students' academic performance. In conclusion, the results of the interview reveal that a number of Libyan postgraduate students are facing some challenges which influenced their academic performance. negatively. The implication of this study suggested that higher education authorities in Libya should improve on their system of delegations and more funds should be allocated to all Libya embassies in various countries, so as to cater for the needs of Libya students followed by continuous supervision and suitable training programs before and after leaving the country.